Adoption of Christ in refugees. Pastoral-canonical guidelines - NECEL, WOJCIECH (Prawo Kanoniczne, 2018)
On the ground of the Erga Migrantes Caritas Christi 2004 instruction, the situation of refugees and expellees requires not only new analyzes and defining their position in the Universal and diocese Churches, but due to the dynamics of the migration phenomenon it is repeatedly necessary to update the pastoral tasks towards these categories of migrants. Political and social unrest in the first two decades of the twenty-first century was a catalyst for the development of the Apostolic See statement: Adoption of Christ in the refugees and forcibly expelled.